Mapping charge-carrier density across the p-n junction in ambipolar carbon-nanotube networks by Raman microscopy - Grimm, Stefan; Zaumseil, Jana (Advanced materials, 2014)
In situ confocal Raman microscopy is used to map the recombination zone (induced p-n junction) in an ambipolar carbon-nanotube-network transistor with high spatial resolution. The shift of the 2D mode (G’ mode) depending on hole and electron accumulation serves as a measure for the local charge-carrier density and provides complementary information about charge transport and recombination in ambipolar transistors.
Gesehen am 20.10.2020